EVALUASI PROGRAM PELATIHAN BAGI PENYULUH PERTANIAN DI BPP KABUPATEN GUNUNGKIDUL (EVALUATE THE TRAINING PROGRAMMES FOR AGRICULTURAL EXTENSION AGENTS IN BPP OF GUNUNGKIDUL REGENCY) - Yulianto, Gunawan (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
This research aims to evaluate the training programmes for Agricultural Extension Agents in BPP of Gunungkidul Regency, concerning : 1)the relevance of traininng programme with participants needs (2) the characteristics of agricultural extension agents (3) the participation of participants (4) the quality of training program implementation (5) the benefit of training programme to participants and (6) the participants skill in extention implementation. This evaluation research using the CIPP model ( Context, Input Process,Product) developed by Stufflebeam. The subject s were 23 participants of agricultural extention agents and 46 persons farmers.The data were collected using questionaire, interveiws and through observations. The quntitative data were analyzed descriptively by using SPSS 11.0 for windows. The validity of the instrument was examined through the content and construct validity by using the factor analyzis.The reliability of the instrument was examined by using the alpha coefficient. The result of the reserarch shows that: (1)The training program is relevant to the participants needs (2) The characteristic of participant 100 % is civil servent functional ofagriculturl exctention agents, formal education of participants is 4,4% SPMA, 39,13 D3 and 56,52 % D4/S1 with experience as agricultural extention agents 86,95% for more than 15 years (3) The participants participation is in an excellent category (90%)(4) The training program implementation quality is in an excellent category (5) benefit for participant is in an excellent category (6) the farmer percived that in general the extenching skill of the agricultural extention agents is in an excellente category and the main constraint in programme implementation is limited availability of supporting facility for activity. Keywords :